Correction: A novel concept of two-component dielectric function for gold nanostars: theoretical modelling and experimental verification. Issue 17 (22nd April 2021) - Khlebtsov, Nikolai G.; Zarkov, Sergey V.; Khanadeev, Vitaly A.; Avetisyan, Yuri A.
Abstract : Correction for 'A novel concept of two-component dielectric function for gold nanostars: theoretical modelling and experimental verification' by Nikolai G. Khlebtsov et al., Nanoscale, 2020, 12, 19963–19981, DOI: ; 10.1039/D0NR02531C .